Constructive-Developmental Theory and the Integrated Domains of Wisdom: Are Post-Conventional Leaders Really Wiser? - Spano, Sharon L. (Integral Review: A Transdisciplinary & Transcultural Journal for New Thought, Research, & Praxis, 2015)
How leaders experience wisdom is important to our understanding of leadership behavior as well as to our overall understanding of leadership. The article explores qualitative findings that may advance academic discourse and research at the intersection between leadership, wisdom, and constructive-developmental theory. The present study examined how 12 executive leaders who assessed at the conventional and post-conventional stages of adult development experience wisdom. It is significant in that it addresses a gap in the literature between wisdom and constructive-developmental theory. Semi-structured interviews were conducted to determine how executive leaders understand their leadership role in terms of the cognitive, reflective, and affective domains of wisdom. Contrary to research that defines and operationalizes wisdom as the integration of these domains, findings indicate that participants experience wisdom in one or more of the domains of wisdom. Participants were also assessed for their meaningmaking capacity to determine their stage of development using the SCTi-Map instrument. Contrary to research in constructive-developmental theory that suggests that postconventional levels of development may equate to higher levels of wisdom, findings also indicate that there was no significant difference between how leaders describe their propensity for wisdom and their measured adult stage of development. Leaders who assessed at both the conventional and post-conventional stages of development described a propensity for wisdom. Analysis of participant responses suggests that the wisdom, in all its complexity, has its own trajectory and therefore necessitates inquiry into the lines of human development to include integral perspectives associated with spiritual, emotional, and psychosocial measures. The results of this study indicate the potential for additional research that explores wisdom in the context of both adult lines and adult stages of development to determine if specific correlations do exist.